2000
DOI: 10.1034/j.1398-9995.2000.00826.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of chronic urticaria

Abstract: exercise. Only oral challenge with a wheatmeal roll followed by an additional exercise test on the bicycle ergometer produced immediate-type reactions. After 20 min, itching of the skin on the neck and back occurred, followed by generalized urticaria with swelling of the upper lip. The patient received intravenous injections of 4 mg of dimetindene maleate and 250 mg of methyl-prednisolone. This relieved the symptoms within minutes. In the literature, 163 cases of fooddependent, exercise-induced anaphylaxis are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…14,15,23,[28][29][30] However, in many studies, challenge with ASA 15,19,[22][23][24][25]28,29,31,32 and ⁄ or ASST 13,19,22,[24][25][26][27]31,32 have not been reported or performed. Finally, many patients were affected by physical urticaria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15,23,[28][29][30] However, in many studies, challenge with ASA 15,19,[22][23][24][25]28,29,31,32 and ⁄ or ASST 13,19,22,[24][25][26][27]31,32 have not been reported or performed. Finally, many patients were affected by physical urticaria.…”
Section: Discussionmentioning
confidence: 99%
“…Anecdotal studies suggested therapeutic effects for antileukotrienes in the treatment of urticaria exacerbations induced by ASA 13 and other nonsteroidal antiinflammatory drugs (NSAIDs) in patients with CU, 14 chronic autoimmune urticaria, 15 acquired cold urticaria, 16,17 delayed-pressure urticaria (DPU), 18 and intractable CU. 19 A single negative study reported a pranlukast-evoked urticaria in patients affected by ASAinduced urticaria; 20 however, this molecule is not marketed in Europe.…”
Section: Anecdotal Series and Open Studiesmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] The effects of LT-RAs in patients with CIU have been evaluated mostly in a heterogeneous population of patients. The majority of the studies reported in the literature are anecdotal reports, and only a few are placebo-controlled studies.…”
Section: 2mentioning
confidence: 99%
“…Anecdotal studies suggested therapeutic effects for antileukotrienes in the treatment of urticaria exacerbations induced by ASA24 and other nonsteroidal anti-inflammatory drugs (NSAIDs) in patients with CIU,25 chronic autoimmune urticaria,26 acquired cold urticaria,27,28 delayed-pressure urticaria (DPU),29 and intractable CIU 30. A single negative study reported a pranlukast-evoked urticaria in patients affected by ASA-induced urticaria 31.…”
Section: Urticaria Treatment With Antileukotrienesmentioning
confidence: 99%